Use of acetyl cysteine in respiratory tract disease in children - Moeljono S. Trastotenojo; Harsoyo N.; Anggoro D. B. Sachro; Said H. W.; A. G. Soemantri (Indonesian Pediatric Society, 1984)
In this study 54 children with respiratory tract disease: bronchopneumonia, bronchial asthma, bronchiolitis and tuberculosis all treated with acetylcysteine and placebo were analysed. In thirty eight patients with bronchopneumonia 20 were treated with acetylcysteine and 16 with placebo; in 9 patients with bronchial asthma 5 were treated with acetylcysteine and 4 with placebo. Of the 5 patients with bronchiolitis, 3 were treated with acetylcysteine and the remainder with placebo. Two children with tuberculosis were given acetylcysteine. The analysis of patients suffering from bronchopneumonia showed no statistically significant difference between acetylcysteine and placebo. Patients with bronchial asthma also showed no significant difference between both groups. There is a statistically significant difference between the results on the first, third, fifth and seventh day of treatment of the group of patients treated with acetylcysteine. No attempts were made to analyse bronchiolitis and tuberculosis. No side effects were seen in this study.